2006
DOI: 10.1038/sj.npp.1301109
|View full text |Cite
|
Sign up to set email alerts
|

Previous Exposure to THC Alters the Reinforcing Efficacy and Anxiety-Related Effects of Cocaine in Rats

Abstract: The hypothesis that prior cannabis exposure increases the likelihood of becoming addicted to other drugs can be evaluated by giving rats a history of tetrahydrocannabinol (THC) exposure, then allowing them to self-administer other drugs. In Experiment 1, THC preexposure did not alter the acquisition of cocaine self-administration or the amount of cocaine taken under a fixed-ratio 1 (FR1) schedule, with one response required for each injection. Under a progressive-ratio schedule, with the response requirement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
2
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 73 publications
4
59
2
5
Order By: Relevance
“…Cocaine is known for exerting both rewarding and anxiogenic effects (Ettenberg, 2004), so the higher selfadministration rates shown by CP-females in our study could reflect either an increase in the rewarding actions of cocaine or a decrement in its anxiogenic effect (Panlilio et al, 2007). There is evidence that fails to support the former speculation.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Cocaine is known for exerting both rewarding and anxiogenic effects (Ettenberg, 2004), so the higher selfadministration rates shown by CP-females in our study could reflect either an increase in the rewarding actions of cocaine or a decrement in its anxiogenic effect (Panlilio et al, 2007). There is evidence that fails to support the former speculation.…”
Section: Discussioncontrasting
confidence: 57%
“…A few studies had examined the causal link between a prior tetrahydrocannabinol (THC) exposure and a subsequent enhanced drug self-administration; however, they used adult THC pre-treated rats that subsequently underwent heroin or cocaine self-administration (Panlilio et al, 2007;Solinas et al, 2004). Since these designs did not incorporate the developmental component that is cardinal to the gateway hypothesis, a full experimental validation of the hypothesis was still missing.…”
Section: Discussionmentioning
confidence: 99%
“…It is popularly debated whether or not chronic cannabis use in humans can promote a neurobiological vulnerability to other drugs of abuse (Kandel et al, 2006;Tarter et al, 2006). In laboratory animal models, experiments have tested the notion that CB 1 receptor agonists such as THC can influence self-administration (Panlilio et al, 2007), conditioned place preference (CPP; Parker et al, 2004) or cross-sensitization to psychostimulants (Arnold et al, 1998;Ellgren et al, 2004). These studies have largely found no evidence that previous exposure to cannabinoids can enhance the rewarding efficacy of cocaine (Arnold, 2005;Panlilio et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report using Sprague Dawley rats, prior exposure to delta-9-THC did not affect the acquisition and subsequent rates of cocaine selfadministration under a fixed-ratio 1 schedule of injection, but did reduce the number of "cocaine-seeking" responses under a progressive-ratio schedule (145). Thus the sensitivity to delta-9-THC exposure may vary with behavioral procedure.…”
Section: Effects Of Cannabinoids On Cocaine-maintained Self-administrmentioning
confidence: 99%
“…In the report by Panlilio and colleagues (145), delta-9-THC pre-exposure also decreased both the number of entries in the center-zone of an open-field arena, and the time spent in the lighted compartment of the dark-light box (two different predictors of an anxiety response) in cocaine-treated rats. The authors suggested that the reduced effectiveness of cocaine as a reinforcer after delta-9-THC pre-exposure may be because the previous exposure to the cannabinoid agonist enhanced the aversive/anxiogenic effects of cocaine (145).…”
Section: Effects Of Cannabinoids On Cocaine-maintained Self-administrmentioning
confidence: 99%